Inadvertent radical nephrectomy leads to worse prognosis in renal pelvic urothelial carcinoma patients: A propensity score-matched study - Wu, Feixiang; Zhang, Pan; Li, Lingxun; Lin, Shiqing; Liu, Jianhong; Sun, Yi; Wang, Yuanlong; Luo, Chengjun; Huang, Yu; Yan, Xiao; Zhang, Meng; Liu, Guixi; et al. (Frontiers in Oncology, 2022)
Objective To compare overall survival (OS) and cancer-specific survival (CSS) in renal pelvic urothelial carcinoma (RPUC) patients treated with radical nephroureterectomy (NU) and inadvertent radical nephrectomy (RN). Patients and methods In this retrospective study, patients with RPUC who underwent NU or RN diagnosed between 2004 and 2017 were identified from the Surveillance, Epidemiology, and End Results database. To adjust the confounders, the propensity score-matched analysis was conducted. The Kaplan–Meier method and log-rank test were performed to explore the effect of different surgical methods on OS and CSS. Results A total of 2197 cases were finally included in this analysis, among which, 187 (8.5%) patients were treated with RN and 2010 (91.5%) patients were treated with NU. Before matching, the survival analysis revealed that the OS (HR: 1.444, 95%CI: 1.197, 1.741) and CSS (HR: 1.522, 95%CI: 1.211, 1.914) of patients who received RN were worse than that of patients who received NU (p = 0.0001 and p = 0.0003, respectively). After matching, the RN group had a worse OS (HR: 1.298, 95%CI: 1.002, 1.682) than the NU group (p = 0.048). No significant difference was observed in CSS between the RN and NU groups (p = 0.282). The hierarchical analysis showed that there was no significant difference observed in OS and CSS in patients with tumor size ≤4.2 cm (p = 0.884 and p = 0.496, respectively). In tumor size >4.2 cm, both OS (HR: 1.545, 95%CI: 1.225, 1.948) and CSS (HR: 1.607, 95%CI: 1.233, 2.095) of patients who received RN were worse than those of patients who received NU (p = 0.0002 and p = 0.0005). Conclusion RN could lead to worse oncological outcomes than NU in patients with renal pelvis urothelial carcinoma. Accurate diagnosis of renal pelvis urothelial carcinoma is extremely important.